Mass Media Competition, Political Competition, and Public Policy - Strömberg, David (Review of Economic Studies, 2004)
If better informed voters receive favourable policies, then mass media will affect policy because mass media provide most of the information people use in voting. This paper models the incentives of the media to deliver news to different groups. The increasing-returns-to-scale technology and advertising financing of media firms induce them to provide more news to large groups, such as taxpayers and dispersed consumer interests, and groups that are valuable to advertisers. This news bias alters the trade-off in political competition and therefore introduces a bias in public policy. The paper also discusses the effects of broadcast media replacing newspapers as the main information source about politics. The model predicts that this change should raise spending on government programmes used by poor and rural voters.